Design and Implementation of Solar Power System on Lettuce Hydroponic Greenhouse in Sekayu Musi Banyuasin Regency South Sumatera Province - Sudarso, Hairad; Taqwa, Ahmad; Kusumanto, RD (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Cultivation of lettuce in a greenhouse is considered a sustainable agricultural technique. Unlike conventional farming, which is susceptible to water shortages, pests, and other uncertainties that can lead to inconsistent and lower-quality lettuce production, hydroponic cultivation in a greenhouse ensures not only high-quality lettuce production but also continuous availability of crops, protected from extreme weather conditions such as droughts and pests. Although greenhouse cultivation is an effective approach, in lowland areas like Sekayu City, the capital of Musi Banyuasin Regency, the microclimate inside the greenhouse can be relatively high and less favorable for lettuce growth. Lettuce ideally thrives in highland regions with a temperature of around 28°C and humidity of 76%. Therefore, it is necessary to control the microclimate inside the greenhouse to optimize lettuce growth. This control requires electrical energy to operate various electronic devices in the microclimate control system, such as exhaust fans and cooling pad water pump. In this study, a solar power electrical system is designed to meet the energy needs for operating a lettuce greenhouse in Sekayu City, Musi Banyuasin Regency, South Sumatra Province. The research was conducted for 31 days, from July 1 to July 31, 2023. The highest power output was recorded on July 31, 2023, at 11 kWh, while the lowest output occurred on July 20, 2023, at 5 kWh. The research utilized an MMPT inverter, which prevents overcharging and maintains a constant 50 A input power when charging the battery. Additionally, an IoT system was used to monitor the performance of the solar power generation system, facilitating data collection on electricity production.